Features Sub-Regional Localities in the Structural-Level Organization of the Economic System - Kurbanov, Artur; Gurieva, Lira K.; Novoselov, Sergey N.; Gorkusha, Oksana A.; Novoselova, Natalia N.; Kovalenko, Alla A. (International Review of Management and Marketing, 2016)
The new paradigm of development of Russia poses the problem of sub-localities identify promising opportunities for economic growth. Municipalities in the region operating in difficult circumstances of post-crisis development, with the majority of undecided strategic guidelines of the Federation, are experiencing an acute shortage of new tools, mechanisms, resources for development. Mixed trends in the development of sub-regional areas, the differentiation of socio-economic potentials of municipalities necessitate the creation of methodological support and develop practical recommendations to identify the most productive areas of the territories of the shortage of resources. Keywords: regional economy, localities, economic growth, resource regions JEL Classifications: P25; P48